SISTEM PENDIDIKAN DI NEGARA CHINA - Abdul Wahab Syakhrani; Bahrianti Bahrianti; Dewi Dewi; Mahmudah Mahmudah; Elisa Rahmadina (CV. ADIBA AISHA AMIRA, 2022)
The education system includes: basic education (basic education), technical and vocational education (technical and vocational education), higher education (higher education) and adult education (adult education). China's basic education consists of: 3 years of PAUD, 6 years of basic education, 3 years of junior secondary education, 3 years of senior secondary education. 2-3 years of higher education at the academy level, 4 years of technical vocational higher education, 4 years of bachelor's degree education, 2-3 years of master's degree education, 3 years of doctoral education. The pattern of the education management system in China is centralized, starting from the central, provincial, municipal levels, including autonomous regions at the municipal level.